Longarm and the missing husband - Evans, Tabor (Evans, Tabor. Longarm, 2015)
"After Bethlehem Bacon's husband goes missing while out surveying on the Wind River Indian Reservation, Deputy U.S. Marshal Custis Long heads out to Wyoming Territory to lead the search. And when the beautiful Beth insists on accompanying him, Longarm finds himself distracted by desire for the sizzling Mrs. Bacon. But bushwhackers' bullets quickly bring Longarm's senses back into sharp focus. Someone is trying to stop them from learning her husband's fate. Once they reach the reservation, Longarm realizes he may have jumped from the frying pan into the fire. With shooters on every bluff, the lawman will have to rely on steely nerves, a quick draw and a steady aim to smoke out the fatback bastards and save their bacon" --